2020
DOI: 10.1128/jvi.01722-20
|View full text |Cite
|
Sign up to set email alerts
|

Viral Subpopulation Screening Guides in Designing a High Interferon-Inducing Live Attenuated Influenza Vaccine by Targeting Rare Mutations in NS1 and PB2 Proteins

Abstract: Influenza A viruses continue to circulate among wild birds and poultry worldwide, posing constant pandemic threats to humans. Effective control of emerging influenza viruses requires new broadly protective vaccines. Live attenuated influenza vaccines with truncations in non-structural protein 1 (NS1) have shown broad protective efficacies in birds and mammals, which correlate with the ability to induce elevated interferon responses in the vaccinated hosts. Given the extreme diversity of influenza virus populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 87 publications
0
30
0
Order By: Relevance
“…For examples, we did not collect data to assess how the extent of mucosal barrier injury ( Li et al, 2018 ) in gut and respiratory sites affected the observed associations among microbiota, influenza virus titers, and innate gene expression profiles. Furthermore, the expression of IFN-α/β/λ and IL-6 genes at high levels may not indicate the production of high amounts of functional proteins, as demonstrated in our recent work where a subpopulation of avian influenza virus blocked the synthesis of IFN-β protein without inhibiting the transcription of IFN-β mRNA ( Ghorbani et al, 2020 ). Moreover, without bacterial metabolite or transcriptome data, it remains unknown if the alteration of bacterial diversity, and abundance and following virus infection in this study indicated functional changes of microbiota.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…For examples, we did not collect data to assess how the extent of mucosal barrier injury ( Li et al, 2018 ) in gut and respiratory sites affected the observed associations among microbiota, influenza virus titers, and innate gene expression profiles. Furthermore, the expression of IFN-α/β/λ and IL-6 genes at high levels may not indicate the production of high amounts of functional proteins, as demonstrated in our recent work where a subpopulation of avian influenza virus blocked the synthesis of IFN-β protein without inhibiting the transcription of IFN-β mRNA ( Ghorbani et al, 2020 ). Moreover, without bacterial metabolite or transcriptome data, it remains unknown if the alteration of bacterial diversity, and abundance and following virus infection in this study indicated functional changes of microbiota.…”
Section: Discussionmentioning
confidence: 93%
“…The treatment group was the experimental unit. Sixteen birds per group were sufficient for statistical comparisons of viral shedding, gene expression, and microbiota data based on our published studies ( Ghorbani et al, 2020 ; Jang et al, 2018 ; Johnson et al, 2018 ; Ngunjiri et al, 2019b ; Taylor et al, 2020 ). Median egg infectious dose (EID 50 ) for each virus stock was calculated prior to normalization of virus concentration on the day of challenge.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative PCR amplicon concentration was determined by uorescence signals detected at the end of each qPCR cycle, and their logarithmic values were plotted against the cycle number as Ct values. Relative mRNA expression levels were calculated as fold changes over the Mock group using the 2 -ΔΔCT method [15].…”
Section: Transcriptional Analysesmentioning
confidence: 99%